2018
DOI: 10.1002/chem.201802585
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Activity of Heterogeneous Cofacial Cobalt Porphyrins for Oxygen Reduction Electrocatalysis through Self‐Assembly

Abstract: We report a suite of coordination-driven self-assembled prisms for heterogeneous electrocatalytic oxygen reduction (ORR) differing in the molecular clips linking two porphyrin faces in a cofacial arrangement. ORR activities and selectivities of monomeric CoTPyP along with cofacial prisms Ox-Co, Oxa-Co, and Benzo-Co were probed using cyclic voltammetry and rotating ring-disk techniques. All species were immobilized as heterogeneous catalysts on glassy carbon electrodes using a Nafion ink method. The selectiviti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…4, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In addition to biologically relevant Fe porphyrins, Co porphyrins have also received great attention because of their high activity and stability. [19][20][21][22][23][24][25][26][32][33][34] However, mononuclear Co porphyrins are much less selective than Fe analogues to catalyze the 4e reduction of O 2 to water. Unlike Fe complexes, Co complexes in general catalyze the 2e reduction of O 2 because the peroxo intermediates of Co are challenging to undergo heterolytic O-O bond cleavage to generate terminal Co-oxo species that have large d electron counts and thus are high in energy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] In addition to biologically relevant Fe porphyrins, Co porphyrins have also received great attention because of their high activity and stability. [19][20][21][22][23][24][25][26][32][33][34] However, mononuclear Co porphyrins are much less selective than Fe analogues to catalyze the 4e reduction of O 2 to water. Unlike Fe complexes, Co complexes in general catalyze the 2e reduction of O 2 because the peroxo intermediates of Co are challenging to undergo heterolytic O-O bond cleavage to generate terminal Co-oxo species that have large d electron counts and thus are high in energy.…”
Section: Introductionmentioning
confidence: 99%
“…34,[41][42][43][44] Additionally, for complexes of late-transition metals, such as Co, it is found that dinuclear complexes are typically more efficient than mononuclear analogues to catalyze the 4e reduction of O 2 . [20][21][22][23][24][25][26][45][46][47][48][49][50][51][52][53] This improvement is likely caused by the formation of peroxo-bridged dinuclear intermediates, 45,47 whose subsequent reduction can result in the 4e ORR. Despite the improvement in the selectivity, however, from mononuclear to dinuclear complexes, the enhancement of catalytic activity, in terms of both catalytic currents and overpotentials, is unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…For example ORR catalyzed by unsubstituted CoPc or by CoPc with the addition of one or more electron-donating or electronwithdrawing substituents adsorbed directly on graphite proceeds via a 2-electron transfer process (Zagal et al, 1992;Sun et al, 2014;Zagal and Koper, 2016;Ye et al, 2017;Abarca et al, 2019) whereas complexes with pendant residues that increase the electron back-bonding would promote a direct 4-e process as in Equation 2 (Steiger and Anson, 1995;Tse et al, 1997;Riquelme et al, 2018a,b). Co-cofacial bimetallic complexes and dimeric Co porphyrins that bind simultaneously both dioxygen atoms would also transfer directly 4 electrons to O 2 (Collman et al, 1980;Durand et al, 1983;Le Mest et al, 1997;Peljo et al, 2012;Swavey and Eder, 2013;Wada et al, 2013;Dey et al, 2017;Oldacre et al, 2018). Penta-coordinated complexes involve a Co center coordinated to 4 planar N atoms and an axial N belonging to a pyridine molecule as for example in VB12 seem to promote a 4-e process.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the central metal atom and potential side groups, porphyrins exist with a wide range of chemical, biological, and electronic functionalities. [8] Owing to their structural flexibility, they find widespread applications in electrocatalysis, [9] sensorics, [10] molecular electronics, [11] molecular mechanics [12] and dye-sensitized solar cells. [13] To be used in devices, the molecules have to be supported on solid substrates.…”
Section: Introductionmentioning
confidence: 99%